Integration of Christian Strategy and Innovative Learning in Christian Religious Education in the Digital Age - Meike Irmawati Tompira; Tonny Andrian Stefanus; Maria Titik Windarti (International Journal of Christian Education and Philosophical Inquiry, 2025)
The transformation of education in the digital age demands an integrative approach between spiritual strategies and learning technologies. This article combines the principles of Jesus' teaching according to Matthew 5–7 and the church's strategies in shaping responsible servant leaders with innovative learning approaches that strengthen the professional competencies of Christian Religious Education (PAK) teachers. The research method used is a literature review of two relevant articles. The results indicate that the integration of spiritual disciplines (such as discipleship, prayer, obedience) and technological innovations (such as flipped learning, blended learning, and game-based learning) contributes to the improvement of contextual Christian education quality. PAK teachers act as agents of transformation to deliver meaningful learning, Christian character, and balanced technological mastery.